Mercy watson is missing! ebook - DiCamillo, Kate (Mercy Watson, 2023)
Every favorite character from Kate DiCamillo's New York Times best-selling Mercy Watson books makes an appearance in this extended, riotously funny series crescendo. When Mercy Watson the pig goes missing, all of Deckawoo Drive is in an uproar. The Watsons are inconsolable, and the local police, fire, and animal control departments are no help whatsoever. Bossy neighbor Eugenia Lincoln is not quite as sad as she might be, but thankfully her sister, Baby Lincoln, has the idea to hire a private investigator. Granted, Percival Smidgely, PI, may be more bumbler than gumshoe, but his pigeon, Polly, is there to point the way. Meanwhile, Frank and Stella Endicott and Stella's friend Horace Broom are ready to do some investigating of their own. Will the clever neighborhood sleuths manage to follow the trail of hoofprints—and a certain overwhelmingly enticing scent—and recover their porcine wonder? With deftly paced narrative comedy, visual slapstick, abundant artwork in both black and white and full color, and warm affection for their cast of characters, Kate DiCamillo and Chris Van Dusen bring us a highly satisfying, extra-special series finale that rewards loyal fans—and invites new readers to explore the stories that came before.